Sharing Responsibility for Divesting from Fossil Fuels. (December 2017) - Godoy, Eric S.
Governments have been slow to address climate change. If non-governmental agents share a responsibility in light of the slow pace of government action then it is a collective responsibility. I examine three models of collective responsibility, especially Iris Young's social connection model, and assess their value for identifying a collective, among all emitters, that can share responsibility. These models can help us better understand both the growth of the movement to divest from fossil fuels and the nature of responsibility for collective action problems. Universities and colleges share a responsibility because they occupy similar positions of, among other things, power and privilege.